STUDI TENTANG MOTIVASI DAN PERSEPSI PENGUNJUNG TERHADAP PENGELOLAAN PEMANFAATAN SATWA SEBAGAI OBYEK WISATA DI TAMAN SATWA PUNTI KAYU PALEMBANG SUMATERA SELATAN - Irwani Gustina Teguh; Eva Rachmawati; Burhanuddin Masy'ud (Media Konservasi, 2010)
Punti Kayu Natural Recreation Park is a tourist area that also serves as a means of protection and conservation of wildlife species. The management of this natural recreation park should be considered because tourist activities is can be cause direct or indirect interference in animals. The aim of this research was to know tourist motivation and perseption about animal welfare  management as tourism in Punti Kayu Animal Park, to identification of potential tourism object based on animal, and to formulate  recomentaion of tourism program and its develpoment.   Research was conducted from July to August 2009 in Punti Kayu Natural Recreation Park. The result of this reseach showed that generally of tourist characterics are kids and old people i.e 35 %,   from Palembang city (77%), as student (39%). Tourism area  more interested by tourist i.e  animal park and lake. Generally motivation of tourist to animal  park (55,6%) are to see animal attraction especially bear and orangutan. Perseption of tourist about animal welfare management in Punti Kayu Animal Park Tourist was well enough.   Tourism program and development plan future based on animal attraction  in the Punti Kayu Natural Recreation Park especially in Animal Park focused on four objects, namely animal parks, recreational parks, lakes, and museum tours fauna. Based on general tourist characteristics were kids and students, the  five tourism activities can be recomendated to develope in Punti Kayu Natural Recreation Park i.e.   Fieldtrip to Punti Kayu, More Introducing  of Macaca, Introducing Water Habitat in  Punti Kayu, Have Fun with Mr. Elephant and  Gives Colours to The Bird. Keywords: animal park, animal welfare, Punti Kayu, touris perseption, tourism activities.